KAJIAN METODE SISTEM NILAI UNTUK MENGEVALUASI PENGADAAN JASA KONSTRUKSI - I B. Putu Bintana; I G. A. Adnyana Putera; I B. Rai Adnyana (JURNAL SPEKTRAN, 2015)
Abstract: The construction procurement evaluation method using lowest price conforming methods often causes some quality problems for  owners and increases the probability of dispute and delay during the contract execution. On the other hand, merit point system evaluation method can provide quality assurance, but the procurement committees are often dificult to apply it, and to determaine mesurable criteria evaluation.Therefore, it is necessary for a more in-depth study to find out the criteria evaluation for construction procurement. The research conducted in Bali, and adopted inductive qualitative approach involving 45 experts participated in construction procurements using merit point system evaluation.Puposive sampling is applied to determine the respondents come from all actors included during procurement process. The data was collected through interviews, observation participant and questionnaires, and the Analytic Hierarchy Process (AHP) is choosed to analyse them. The result shows that : the merit point system evaluation for construction procurement can determine the contractor provides better quality than the lowest price conforming method when theevaluation criteria are clear, mesurable and transparant in the bidding document. There are two principle aspects that must be considered to assurethe quality that is: the technical aspect and the cost that weight consecutively 60% and 40%. The technical aspect comprises of : a) the existance of work plan (13.51%), comprising of construction methods (4.12%), supporting  equipment (4.05%), supporting material (3.46%), suporting workers (1.88%); b) competencies of human recources (19.91%), comprising of project management competencies(2.31%), existence of expert (7.92%) and certificated human resources (9.68%); c) existence of supporting equipments (15.54%) consisted of lifting support (4.79%), transportation support (6.17%), surveying support equipment(4.58%); d) the existing of time management (6.30%) consisted of network planning (4.13%), bar chart (1.03%), and S-curve (1.14%); and e) existence of quality assurance (2.14%) consisted of quality management system (1.95%), performance quality management (0.66%) and material management quality (2.14%). From price point of view, it must be evaluated the faireness of price and price offer that weighs consecutively 25.66% and 14.34%.